Vibration Investigation On Rotational Pumps At UTHM Biodiesel Pilot Plants - Mohammad Noor, Noor Akmal; Rahmad, Rohani (Progress in Engineering Application and Technology, 2023)
Vibration is an unavoidable reality in machinery and equipment. Therefore, it was essential in investigated the vibration phenomena occurring in the rotating equipment to maintain its performance. The research aimed to study the different specifications of the rotating pump’s vibration in determining the fault occurrence prediction and correlation of temperature fluid to the pump’s vibration. Based on the ISO-10816 standard, the pump safe limit was identified, and the pump operation was decided to continue to run, stop immediately, or undergo maintenance. In determining the type of maintenance, the pump’s fault was investigated individually based on the characteristics shown in the Fast Fourier Transform (FFT) waveform. If the safe limit condition is exceeded, the maintenance is done according to the fault diagnostic test. The experiment shows that pump A must stop immediately, undergo alignment maintenance, and change the rubber bush since it generated a vibration velocity of more than 2.80 mm/s (safe limit standard for motor less than 5kW power). In contrast, pumps B, C, and D are acceptable because vibration velocity is lower than 2.80 mm/s. The effect of temperature fluid (25℃ to 70℃) was studied during the occurrence of vibration. The results indicated the vibration velocity increased by 38%, 22%, 64%, and 21% at four (4) measured points as the fluid temperature increased when flowing in the pump. The significant causes of these problems were the lower viscosity of the fluid and the decreasing pump’s stiffness